STUDY OF BIOPHILIC CONCEPT IN PONDOK INDAH BINTARO HOSPITAL - Rahman, Izzat Fadhlur; Lissimia, Finta (Border: Jurnal Arsitektur, 2022)
A hospital is a medical facility that aims to improve the quality of life of the community through the process of preventing, treating, and medicating health problems. The mix of hope for recovery and the risk of death creates the impression that the hospital is a scary place, which affects the patient's psychological condition and causes other problems. Biophilic is an architectural approach that aims to have a positive influence on the human psyche by fulfilling his instinctive need for affiliation with nature. This study aims to understand the application of the biophilic concept at Pondok Indah Bintaro Hospital. The method used is descriptive qualitative with analysis based on the theory of 14 biophilic patterns by Browning, Ryan, and Clancy, through a hospital with a biophilic architecture that represents natural systems at a site scale through nature in space. At the building scale, biophilic is applied through architectural details that analogize natural forms (nature analogues), as well as natural spatial characteristics that affect human perception (nature of space).